Discrete mathematics and its applications - Rosen, Kenneth H.; Krithivasan, Kamala (McGraw-Hill, 2013)
Intends to meet the needs of international students of discrete mathematics. This title covers chapters such as: Boolean Algebra and Modeling Computation; and, revised problems for the international student integrating alternative methods and solutions.